Analisis Komunikasi Interpersonal Pustakawan Dalam Mempersiapkan Akreditasi Di Perpustakaan Pusat Universitas Islam Negeri Raden Intan Lampung - Eriq Tirta Ayatama; Ahmad Basyori; Mustofa, Muhamad Bisri (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
This study aims to analyze the role of interpersonal communication among librarians in supporting the successful preparation of accreditation at the Central Library of Universitas Islam Negeri Raden Intan Lampung. Interpersonal communication is considered a crucial factor in creating effective coordination, accelerating document preparation, and fostering solid teamwork among librarians. This research employs a qualitative descriptive approach, utilizing data collection methods such as direct observation, in-depth interviews with librarians, and documentation review related to the accreditation process. Data analysis is conducted descriptively to provide a detailed depiction of communication dynamics, encountered obstacles, and strategies implemented by librarians during the accreditation preparation. The findings reveal that effective interpersonal communication significantly contributes to smooth coordination and synergy among librarians, despite challenges such as differences in communication styles and limited time availability. The use of digital communication technologies and interpersonal skills training emerge as important solutions to overcome these barriers. This study concludes that strengthening interpersonal communication is a key factor in the success of accreditation preparation and in enhancing the overall quality of library services. These findings provide a foundation for developing communication management and human resource training in academic libraries moving forward. This paper specifically highlights the role of librarian interpersonal communication in the context of library accreditation preparation, including its relation to teamwork dynamics and user perceptions.